"O Caminho da superação a nível pessoal e profissional" - Marília da Silva Oliveira (2021)
The Professional Traineeship is an integral part of the 2nd year of the Master's Degree in Teaching Physical Education in Primary and Secondary School in the Faculdade de Desporto of the University of Porto and corresponds to the last stage of this academic journey. This was held in the 2020/2021 school year, at the Cooperating School. This paper presents a critical and reflected description of the various learnings, interactions and experiences lived throughout this academic year, which contributed to the professional and personal development of the trainee student. The traineeship is an extremely important stage, where the first contact with the teaching of Physical Education in school arises and allows us to put into practice all the knowledge previously acquired. This report is divided into six parts, starting with the introduction, which provides an overview of the objectives of this document. The second point refers to the trainee student's personal background regarding the choice of this Master's Degree, initial expectations and views about this job. This is followed by a description of the institutional framework where a reflection of the importance of the school and the characterization of the Cooperating School is made, as well as the assigned classes and of the Traineeship Nucleus. The fourth point contemplates the practice and it's divided into six topics related to this comprehensive point. Point five includes professional development, which conveys the research study on Non-Verbal Communication. Finally, there is the sixth and last point, presenting the final considerations and perspectives for the future of the trainee student.